2013
DOI: 10.1111/sji.12044
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Branched α‐Oligomannoside Structures on Induction of Anti‐Candida Humoral Immune Response

Abstract: Several studies have established the potential efficacy of humoral immunity, primarily mannan-specific antibodies, in host protection against major fungal pathogen Candida albicans. In this study, we analysed humoral immune response induced by immunization with BSA-based conjugates bearing synthetic a-1, 6-branched oligomannosides (pentamannosides (M5) or hexamannosides (M6)) mimicking antigenic sequences of Candida cell wall mannan. We analysed the ability of antibodies prepared by immunization to recognize r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…In addition, our previously published studies revealed structure‐dependent immunogenicity of synthetic oligomannoside–BSA conjugates and capability of vaccination‐induced polyclonal sera to improve candidacidal activity of leucocytes (Paulovičová et al ., ) and polymorphonuclear leucocytes (Paulovičová et al ., , ) in vitro . Results obtained with branched oligomannoside–BSA conjugates (M5‐1, M5‐2 and M6) revealed a lower ability to induce antibodies, significantly enhancing candidacidal activity in comparison with linear oligomannoside–BSA conjugates (M2 and M7‐A; Paulovičová et al ., , , , ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, our previously published studies revealed structure‐dependent immunogenicity of synthetic oligomannoside–BSA conjugates and capability of vaccination‐induced polyclonal sera to improve candidacidal activity of leucocytes (Paulovičová et al ., ) and polymorphonuclear leucocytes (Paulovičová et al ., , ) in vitro . Results obtained with branched oligomannoside–BSA conjugates (M5‐1, M5‐2 and M6) revealed a lower ability to induce antibodies, significantly enhancing candidacidal activity in comparison with linear oligomannoside–BSA conjugates (M2 and M7‐A; Paulovičová et al ., , , , ).…”
Section: Resultsmentioning
confidence: 99%
“…M6-BSA conjugate induced markedly higher levels of mannan-specific IgG compared to the M5-BSA conjugate. In contrast to the M5-BSA conjugate, the M6-BSA conjugate induced immunoglobulin isotype class switch from IgM to IgG, as revealed also from Elispot analysis [ 115 ].…”
Section: Mycosismentioning
confidence: 99%
“…The tested fungal vaccines have a wide range of compositions ranging from whole fungal cells and inactivated organisms to subcellular vaccines based on Candida cell wall mannan , synthetically prepared oligomannosides conjugated to carrier protein or oligomannoside conjugated to single recombinant peptide fragment . Advanced trends in prophylactic and therapeutic possibilities for fungal infections are directed to development of subunit vaccines composed from single specific and immunologically active cell wall‐derived antigens.…”
Section: Glycocojugate Vaccines Based On Candida Cell Wall Mannan‐dermentioning
confidence: 99%
“…Despite the presumption that α‐1,2 linked oligomannosides represent epitopes that induce non‐protective antibodies, several glycoconjugates based on synthetically prepared α‐1,2 linked oligomannosides (Table ) have been prepared and their immunomodulatory properties analyzed . It has been shown that these prepared conjugates are able to stimulate cytokine production of splenocytes in vitro and induce a specific antibody response in vivo .…”
Section: Glycocojugate Vaccines Based On Candida Cell Wall Mannan‐dermentioning
confidence: 99%
See 1 more Smart Citation